Software architecture fundementals. Part 3, soft skills: problem solving, decision making, refactoring, productivity & communications - Ford, Neil; Richards, Mark; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"In Part III of this acclaimed video series on software architecture fundamentals, Neal Ford and Mark Richards turn their focus to the often-neglected area of soft skills. Knowing the ins and outs of programming and technology is only one side of a software architect's skillset. Aside from being an excellent developer, you also have to be a leader. Soft skills help you work well within a larger corporate structure, manage teams, and ensure that technology is a first-level concern at your company."--Resource description page.
Title from title screen title (viewed April 3, 2015).
Presenter, Mark Richards, Neil Ford.
Keywords: Software architecture; Electronic books